Synergy of Dietary Quercetin and Vitamin E Improves Cecal Microbiota and Its Metabolite Profile in Aged Breeder Hens - Amevor, Felix Kwame; Cui, Zhifu; Du, Xiaxia; Feng, Jing; Shu, Gang; Ning, Zifan; Xu, Dan; Deng, Xun; Song, Weizhen; Wu, Youhao; Cao, Xueqing; Wei, Shuo; et al. (Frontiers in Microbiology, 2022)
In the present study, the synergistic effects of quercetin (Q) and vitamin E (E) on cecal microbiota composition and function, as well as the microbial metabolic profile in aged breeder hens were investigated. A total of 400 (65 weeks-old) Tianfu breeder hens were randomly allotted to four experimental groups (four replicates per group). The birds were fed diets containing quercetin at 0.4 g/kg, vitamin E (0.2 g/kg), quercetin and vitamin E (QE) (0.4 g/kg and 0.2 g/kg), and a basal diet for a period of 10-wks. After the 10-wks experimental period, the cecal contents of 8 aged breeder hens per group were sampled aseptically and subjected to high-throughput 16S rRNA gene sequencing and untargeted metabolomic analysis. The results showed that the relative abundances of phyla Bacteroidota, Firmicutes, and Actinobacteriota were the most prominent among all the dietary groups. Compared to the control group, the relative abundance of the families Bifidobacteriaceae, Lachnospiraceae, Tannerellaceae, Mathonobacteriaceae, Barnesiellaceae, and Prevotellaceae were enriched in the QE group; and Bacteroidaceae, Desulfovibrionaceae, Peptotostretococcaceae, and Fusobacteriaceae were enriched in the Q group, whereas those of Lactobacillaceae, Veillonellaceae, Ruminococcaceae, Akkermansiaceae, and Rikenellaceae were enriched in the E group compared to the control group. Untargeted metabolomics analyses revealed that Q, E, and QE modified the abundance of several metabolites in prominent pathways including ubiquinone and other terpenoid-quinone biosynthesis, regulation of actin cytoskeleton, insulin secretion, pancreatic secretion, nicotine addiction and metabolism of xenobiotics by cytochrome P450. Furthermore, key cecal microbiota, significantly correlated with important metabolites, e.g. (S)-equol positively correlated with Alistipes and Chlamydia in E_vs_C, and negatively correlated with Olsenella, Paraprevotella, and Mucispirillum but, a contrary trend was observed with Parabacteroides in QE_vs_C. This study establishes that the synergy of quercetin and vitamin E alters the cecal microbial composition and metabolite profile in aged breeder hens, which lays a foundation for chicken improvement programs.